HUBUNGAN POLA ASUH ORANG TUA DENGAN KREATIVITAS ANAK USIA 5-6 TAHUN - Tresa Ayu; Marmawi Marwawi; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the relationship of parenting style with the creativity of children aged 5-6 years in Kindergarten Bruder Melati Pontianak. The research method used is correlational with quantitative research forms. A sample of 67 respondents was taken from a total population of 81 who were calculated using the solvin technique. The data collection technique used a questionnaire for upbringing and observation for creativity. The data analysis technique uses inferential statistics, with hypothesis testing using the product moment. The results showed 1) there is a positive relationship because r = 0.11 category is very weak and insignificant because r count= 0.96 while r table= 2.00 between authoritarian parenting and creativity, 2) there is a positive relationship because r= 0 , 14 categories are very weak and insignificant because r count= 1.14 while r table= 2.00 between permissive parenting and creativity, 3) there is a significant positive relationship between authoritarian parenting and creativity, because r= 0.69 and r count= 7.83 strong category. The conclusion of this study is that democratic parenting has a positive and significant strong category relationship with creativity, so ha is accepted and h0 is rejected.Keywords: Creativity, Parenting, Relationships